Characterization of a New Fiber from Cyperus Dichrostachus A.Rich Plant - Belete Baye; Tamrat Tesfaye (Advances in Materials Science and Engineering)
Natural fibers have been good substitute sources for swapping synthetic fibers and reinforcing polymer matrices because of their contributions in maintaining ecology, low energy requirement for processing, and maintaining sustainability issues. The aim of this study was to characterize a new fiber from Cyperus Dichrostachus A.Rich (CDA) plant. The CDA plant is a perennial nonwoody grass found in Ethiopian high lands and river basins. The fiber from this plant has a chemical composition of cellulose (60.27%), hemicellulose (22.72%), and lignin (16.59%) contents. It has a density of 1010 kg/m3 and good tenacity of 105.76 cN/Tex with low elongation of 4.88%. The thermal stability of Cyperus Dicrostachus A.Rich fiber (CDAF) was studied using TGA and DTG analyses and revealed that the cellulose degraded at a temperature of 377.1°C. Fourier transform-infrared spectroscopy analysis confirmed that CDAF is rich in cellulose content. Additionally, CDAF can play a vital role as a new reinforcement material and best alternative in bio composite industries. This will give competitive advantages when evaluated with other natural fibers and reveal that there are significant potential benefits in implementation of “cleaner production” in textile material production industries. Specifically, the replacement of synthetic fiber source with renewable biomass will reduce the environmental impact of these fibers. The future study will be focused on investigating the possible valorization route, especially in paper board, composite reinforcement, and bio composite applications.